PENGARUH MOTIVASI, KOMPETENSI, LINGKUNGAN SOSIAL DAN INTERAKSINYA DENGAN FACEBOOK TERHADAP SIKAP PEMBELAJARAN SISWA SMK STUDI KASUS SMK BONAVITA TANGERANG - Dedy Iskandar; Nasril Sany; Andi Saputra (CCIT Journal, 2014)
This study aims to determine the influence of motivation, competence, social environment and interaction with the facebook for high school students learning attitude. The study was conducted in August 2013 in SMK Bonavita Tangerang Jl. Kanjeng Dalam Tangerang, using survey methods. As a sample of this study is the purity of high school students selected (purposive sampling). This research conducted at the beginning of the school year 2012 / 2013 which includes all high school students Purity of class X, XI and XII Multimedia. Results of hypothesis testing showed that the final model obtained in this study is that facebook is very influential on high school students learning attitude Purity. Variable LS (social environment) are influenced by variables moderasinya (LSFB) affect the ATTITUDE variable. The influence of variables interact with the variable FB LS (social environment) affect the variable Attitude. Has a degree of influence of 0.511 (51.1%). The methode of this research is interview, observation and literatur.